Living Hadith in the Bari'an Ritual of Sidodadi Society - Sri Purwaningsih; Thiyas Tono Taufiq; Muhammad Faiq (UIN Sunan Kalijaga Yogyakarta, 2021)
This research is conducted to comprehend the typology of living Hadith in Indonesia based on the ritual-based Hadith in Sidoadi’s society. The ritual-based Hadith called Bari’an ritual. the Sidodadi's people have been trying to preserve the Bari'an ritual. This ritual is related to a major change in the history of the Dudak village, which is now called Sidodadi. This study focuses on how the views of the Sidodadi's people on the Bari'an ritual, the ritual forms of Bari'an in Sidodadi, the meanings of the present Bari'an rituals, and its relevance to the values of the Hadith. This is a socio-cultural study with a phenomenological analysis approach. The problem is answered based on qualitative data with the technique of interpretation of emic and ethics. With such emic and ethical interpretation techniques, it can be seen that the forms of the Bari'an ritual in Sidodadi historically have shifted including its motive, meaning, as well as values. The shift is caused by a transformation of the beliefs of Sidodadi's people from Islam 'Kejawen' (Javanese Islam) filled with myths, superstition, and sesaji, turned into Popular Islam filled with values of Hadith.